Access the differences in the job preferences between young graduates in China - ZENG, SHIHAO (2017)
As the result of the explosion in the number of graduates, work places not only have experienced great changes but also tend to be more diversified in employee construction. There are increasing awareness on the importance of job preferences, which could help organisations to promote their recruitment, management and employee performance. The research aims to narrow the gap in job preference in the Chinese context and gain knowledge about the differences between the overseas and domestic graduates. The quantitative approach is adopted to analyse the data which is collected by self-administered questionnaires. The 11 job preferences which have been widely discussed by previous studies in the Western context are selected to test the relationships with gender, generation, education level and overseas experiences. The results are consistent with some previous studies. The main finding of this study is that overseas and domestic graduates significantly differ in the preferences for type of work, company and co-worker.